Meaningfulness and attachment: what dreams, psychosis and psychedelic states tell us about our need for connection - Fischman, Lawrence (Frontiers in Psychology, 2024)
The human need to find meaning in life and the human need for connection may be two sides of the same coin, a coin forged in the developmental crucible of attachment. Our need for meaningfulness can be traced to our developmental need for connection in the attachment relationship. The free energy principle dictates that in order to resist a natural tendency towards disorder self-organizing systems must generate models that predict the hidden causes of phenomenal experience. In other words, they must make sense of things. In both an evolutionary and ontogenetic sense, the narrative self develops as a model that makes sense of experience. However, the self-model skews the interpretation of experience towards that which is predictable, or already “known.” One may say it causes us to “take things personally.” Meaning is felt more acutely when defenses are compromised, when the narrative self is offline. This enables meaning-making that is less egocentrically motivated. Dreams, psychosis, and psychedelic states offer glimpses of how we make sense of things absent a coherent narrative self. This has implications for the way we understand such states, and lays bare the powerful reach of attachment in shaping what we experience as meaningful.